EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DAN PAIRS CHECK DENGAN PENDEKATAN SAINTIFIK PADA MATERI FUNGSI DITINJAU DARI ADVERSITY QUOTIENT SISWA KELAS VIII SMP NEGERI SE-KABUPATEN SUKOHARJO TAHUN PELAJARAN 2014/2015 - Hafidhah, Tien Syarifah; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was to determine the effect of learning models on the knowledge and skill aspect viewed from adversity quotient (AQ). The learning models compared were learning model of the Numbered Heads Together (NHT) with scientific approach, Pairs Check (PC) with scientific approach, and classical with scientific approach. This research was a quasi-experimental research. The population of the research was all of the eighth grade students of the State Junior High School in Sukoharjo. The instruments used to collect data were mathematics knowledge aspect test, mathematics skill aspect test and adversity quotient questionnaire. Technique of analyzing data that used was unbalanced two ways multivariat analysis of variance. From the research, it can be concluded that: (1) learning by using cooperative learning model of NHT with scientific approach gave the same knowledge and skill aspect with learning by using cooperative learning model of PC with scientific approach, learning by using cooperative learning model of NHT with scientific approach gave the same knowledge and skill aspect with learning by using classical learning with scientific approach, learning by using cooperative learning model of PC with scientific approach gave better knowledge and skill aspect than learning by using classical learning with scientific approach, (2) students who have adversity quotient of Climber gave better knowledge and skill aspect than students who have adversity quotient of Camper and Quitter, students who have adversity quotient of Camper gave the same knowledge and skill aspect with the students who have adversity quotient of Quitter, (3) on each learning model, students who have adversity quotient of Climber gave better knowledge and skill aspect than students who have adversity quotient of Camper and Quitter, students who have adversity quotient of Camper gave the same knowledge and skill aspect with the students who have adversity quotient of Quitter, (4) on each adversity quotient, learning by using cooperative learning model of NHT with scientific approach gave the same knowledge and skill aspect with learning by using cooperative learning model of PC with scientific approach, learning by using cooperative learning model of NHT with scientific approach gave the same knowledge and skill aspect with learning by using classical learning with scientific approach, learning by using cooperative learning model of PC with scientific approach gave better knowledge and skill aspect than learning by using classical learning with scientific approach.Keywords: cooperative learning model, NHT, PC, classical learning, scientific approach, knowledge aspect, skill aspect.